A Proposta Curricular de Geografia do Estado de São Paulo e seus impactos no trabalho docente: um estudo de caso - Gomes, Francisco Eudes (2016)
This research aimed to understand the impacts of Programa São Paulo Faz Escola (Program São Paulo Makes School) has produced within the São Paulo’s public schools during 2008-2014 period. The Brazilian public school has adhered to the current reform fundaments which are notably related into some pedagogical competences. It is noticed, during its practice, the booklets sent to schools which were created to didactically guide the teacher, just ends removing teacher’s autonomy because they have too many detailed procedures. To understand these changes, the concepts of curriculum and educational reform, understood in its historical context, were used to guide the research. The research sources used were some Public School official documents located in São Paulo East Zone, during the period of 2008-2014, and 33% of São Paulo Public School geography teacher interviews. In addition to these sources it was also considered documents produced by the mentioned authors who study the subject. During the research process it was noticed the observation importance and school transformation process analysis which were happening. The reason which justifies this paper is the desire to contribute with information which may be significant for the next new generation formation. External evaluations, such as SARESP, indicate this program (Programa São Paulo Faz Escola) does not have contributed to achieving the objectives appointed by the government, yet